Can previously sedentary females use the feeling scale to regulate exercise intensity in a gym environment? an observational study. Issue 1 (December 2015) - Hamlyn-Williams, Charlotte; Tempest, Gavin; Coombs, Sarah; Parfitt, Gaynor
Abstract Background Recent research suggests that the Feeling Scale (FS) can be used as a method of exercise intensity regulation to maintain a positive affective response during exercise. However, research to date has been carried out in laboratories and is not representative of natural exercise environments. The purpose of this study was to evaluate whether sedentary women can self-regulate their exercise intensity using the FS to experience positive affective responses in a gym environment using their own choice of exercise mode; cycling or treadmill. Methods Fourteen females (24.9 years ± 5.2; height 166.7 ± 5.7 cm; mass 66.3 ± 13.4 kg; BMI 24.1 ± 5.5)) completed a submaximal exercise test and each individual's ventilatory threshold ( V ˙ T $$ \dot{V}T $$ ) was identified. Following this, three 20 min gym-based exercise trials, either on a bike or treadmill were performed at an intensity that was self-selected and perceived to correspond to the FS value of +3 (good). Oxygen uptake, heart rate (HR) and ratings of perceived exertion (RPE) were measured during exercise at the participants chosen intensity. Results Results indicated that on average participants worked close to their V ˙ T $$ \dot{V}T $$ and increased their exercise intensity during the 20-min session. Participants worked physiologically harder during cycling exercise. Consistency of oxygen uptake, HR and RPE across the exercise trials was high. Conclusion The data indicate that previously sedentary women can use the FS in an ecological setting to regulate their exercise intensity and that regulating intensity to feel 'good' should lead to individuals exercising at an intensity that would result in cardiovascular gains if maintained.